Forest conversion to oil palm compresses food chain length in tropical streams - Clare L. Wilkinson; Kenny W. J. Chua; Roswitha Fiala; Jia, Huan Liew; Victoria Kemp; Arman Hadi Fikri; Robert M. Ewers; Pavel Kratina; Darren C. J. Yeo (Wiley, 2021)
In Southeast Asia, biodiversity-rich forests are being extensively logged and converted to oil palm monocultures. Although the impacts of these changes on biodiversity are largely well documented, we know addition to samples we collected in 201 little about how these large-scale impacts affect freshwater trophic ecology. We used stable isotope analyses (SIA) to determine the impacts of land-use changes on the relative contribution of allochthonous and auto chthonous basal resources in 19 stream food webs. We also applied compound-specific SIA and bulk SIA to determine the trophic position of fish apex predators and meso-predators (invertivores and omnivores). There was no difference in the contribution of autochthonous resources in either consumer group (70–82%) among streams with different land-use type. There was no change in trophic position for meso-predators, but trophic position decreased significantly for apex predators in oil palm plantation streams compared to forest streams. This change in maximum food chain length was due to turnover in identity of the apex predator among land-use types. Disruption of aquatic trophic ecology, through reduction in food chain length and shift in basal resources, may cause significant changes in biodiversity as well as ecosystem functions and services. Understanding this change can help develop more focused priorities for mediating the negative impacts of human activities on freshwater ecosystems